PERANAN DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN BENGKALIS DALAM PENEMPATAN TENAGA KERJA LOKAL DI KECEMATAN MANDAU - Aulia, Isnai; Rusli, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The role of the Department of Manpower and Transmigration Bengkalis in local employment in the District Mandau . And the purpose of this study was to determine the role of the Department of Manpower and Transmigration Bengkalis in local employment in the District and to identify factors Saber - inhibiting factors in local employment in the District Mandau . This study used qualitative research methods to the assessment of descriptive data . In collecting the data , the researcher used interview techniques , observation and study of literature . By using key informants as a source of information . Based on the research that has been conducted based on the concept and theory researchers found that the role of the Department of Manpower and Transmigration in local employment in the District Mandau belim effective . This can be seen by the number of registered jobseekers can not be suppliedto companies operating in District Mandau. Keywords : Roles , organization , manpower placement , Efektiftas Organizations